Learning across Generations in Europe: Contemporary Issues in Older Adult Education (Research on the Education and Learning of Adults, 2014)
Learning across Generations in Europe: Contemporary issues in older adult education constitutes an important book in the emergent field of study of older adult learning. The book gives a clear and wide overview on the different concepts, ideas, and meanings, related to older adults' education, learning and intergenerational learning through strong theoretical standpoints, empirical research, and policy directions. Readership: Educational Researchers and their students